Grain growth in nanograined aluminum oxide by high-pressure torsion: Phase transformation and plastic strain effects. (15th July 2018) - Fujita, Ikuro; Edalati, Kaveh; Sauvage, Xavier; Horita, Zenji
Abstract: Application of severe plastic deformation (SPD) to different materials usually leads to significant grain refinement and accelerated phase transformations. This study reports the occurrence of grain growth in nanocrystalline Al2 O3 by SPD processing via high-pressure torsion (HPT) due to a phase transformation from γ with the cubic structure to α with the rhombohedral structure. This transformation was significantly enhanced by pressure and plastic strain and occurred at 650 K below the γ → α transition temperature. The γ phase after HPT processing could be detected only in nanograins or in the nano-sized laths with the (1 3 ¯ 1)γ//(01 4 ¯ )α and [001]γ//[100]α coherent orientation relationship. Graphical abstract: Unlabelled Image